TEKS DAN KONTEKS KITAB HADIS MELAYU PALEMBANG - Muhtasor, Alimron; Agil Husin Al-Munawar, Said; Suyitno; Maryaman; Mat Zain, Farid (Jurnal Lektur Keagamaan, 2023)
ABSTRACT This study examined the manuscript titled "Sir?j al-Makrifat," authored by Muhammad Najib bin Kiagus Muhammad Sholeh in the year 1285 H/1868 AD. Further studies on hadith books produced by Palembang scholars, particularly on this kitab were still scarce. It employyed a philological approach, which includes inventorying, providing detailed descriptions, conducting transliterations and editing text. Data analysis was conducted through the method of hadith criticism, focusing on the aspects of sanad (chain of narrators) and matan (content of the hadith). This involves undertaking takhrij hadith (identifying sources of a hadith), i`tibar sanad (evaluating the chain of narrators), analyzing sanad and matan, and concluding the quality of the hadith. The findings of this study suggest that Palembang scholars have made significant contributions to hadith studies, particularly in preserving the tradition of authentic hadith narration. The book "Sir?j al-Makrifat" was a proof of the intellecttual legacy of Palembang scholars in the field of hadith. It comprises a collection of 206 hadiths of the Prophet SAW about Fadha'il A'mal (virtues of deeds), Targhib (desire for reward), and Tarhib (fear of punishment). A critical analysis of the authenticity of the hadiths of worship found in the book revealed that, of the 100 hadiths studied, 24 are shahih (authentic), 8 are hasan (good), 22 are dha'if (weak), and 19 are maudhu' (fabricated). The status of the other 27 hadiths remains unknown. A comparison of "Sir?j al-Makrifat" with the manuscripts MS 63, MS 595, A625, and EAP212/4/2 revealed common themes in hadith books across the archipelago, specifically the Targhib wa Tarhib pattern, which includes hadiths on Fadha'il A'mal and morals. However, Sir?j al-Makrifat appears more philologically comprehensive when compared to other manuscripts. This is evidenced by the book title written in the text and the colophon of the manuscript, which includes the author's name and the year the manuscript was written. Keywords: Malay Hadith Book, Sir?j al-Makrifat, Palembang scholars   ABSTRAK Studi ini membahas naskah Sir?j al-Makrifat karya Muhammad Najib bin Kiagus Muhammad Sholeh yang ditulis pada tahun 1285 H/1868 M. Kajian mendalam terhadap kitab hadis karya ulama Palembang ini belum banyak dikaji oleh para peneliti sehingga sangat penting untuk dilakukan dalam upaya untuk memberikan perhatian yang memadai terhadap keulamaan Palembang dan kontribusinya di bidang hadis. Penelitian ini menggunakan naskah sebagai sumber utama kajiannya, karenanya pendekatan filologi yang dilakukan adalah inventtarisasi naskah, deskripsi naskah, transliterasi dan suntingan teks. Adapun analisis datanya menggunakan metode kritik hadis yang mencakup aspek sanad dan matan dengan tahapannya adalah melakukan takhrij hadis, i`tibar sanad, analisis sanad, analisis matan dan menyimpulkan kualitas hadis. Hasil penelitian menemukan bahwa Palembang mempunyai kontribusi besar dalam bidang kajian hadis, terutama dalam menjaga tradisi  periwayatan hadis bersanad; kedua, Kitab Sir?j al-Makrifat sebagai salah satu warisan intelektual ulama Palembang di bidang hadis berisikan kumpulan 206 hadis Nabi SAW tentang Fadha’il A’mal, Targhib dan Tarhib dan Analisis terhadap keotentikan hadis-hadis ibadah pada kitab Sir?j al-Makrifat menghasilkan temuan bahwa dari 100 hadis yang diteliti, ada 24 hadis yang shahih, 8 hadis hasan, 22 hadis dha’if dan 19 hadis maudhu’, serta 27 hadis yang belum diketahui statusnya; ketiga, berdasarkan perbandingan antara kitab Sir?j al-Makrifat dengan naskah MS 63, MS 595, A625 dan EAP212/4/2 ditemukan adanya kesamaan tema utama dari kitab-kitab hadis di Nusantara yaitu pola Targhib wa Tarhib yang memuat hadis-hadis Fadha’il A’mal dan akhlak. Meskipun demikian secara filologis naskah Sir?j al-Makrifat relatif lebih lengkap dibandingkan dengan naskah lainnya dibuktikan dengan adanya judul kitab yanag tersurat pada teks dan terdapat kolofon naskah yang menginformasikan nama penulis dan tahun penulisan naskah.   Kata kunci: Kitab Hadis Melayu, Sir?j al-Makrifat, Ulama Palembang